Improving Students' Creative Thinking Ability by Applying Project Based Learning in Mathematics Learning - Intan Juniarmi (Aksioma Education Journal, 2024)
This study aims to explore the impact of implementing Project Based Learning (PJBL) in improving students' creative thinking skills in mathematics learning at upper secondary schools. The research method used was a pre-test post-test control group experimental research design, which involved two groups of students: an experimental group that applied PJBL and a control group that received mathematics learning with conventional methods. The research instruments used were creative thinking ability test, observation, and interview. The results showed that students who engaged in mathematics learning with PJBL experienced a significant improvement in their creative thinking ability compared to students who followed conventional learning. In addition, interviews with students and teachers also showed that PPA provided a more interesting and relevant learning experience for students, and enabled the development of creative thinking skills effectively. These findings provide strong support for the use of PPA as an effective learning strategy in improving students' creative thinking ability in mathematics learning in the school environment.